Endoscopic ultrasound-guided radiofrequency ablation for hepatocellular carcinoma in cirrhosis: a case report test for efficacy and future perspectives - de Nucci, Germana; della Corte, Cristina; Reati, Raffaella; Imperatore, Nicola; Arena, Ilaria; Larghi, Alberto; Manes, Gianpiero (Endoscopy International Open, 2020)
Background The percutaneous approach allows for effective and safe treatment of liver lesions. But in case of subcapsular or left segments location, this approach seems to be less effective or unsafe. Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) is a new technique used to treat pancreatic and neuroendocrine tumors in patients unfit for surgery.Methods Hereby, we describe the case of a 70-year-old patient with cirrhosis with a large subcapsular hepatocellular carcinoma (HCC) in II-III-IVb segments, in which surgery or percutaneous therapies were not feasible, treated with EUS-RFA. The HCC was treated using an EUS-RFA (EUSRA) system, which consists of a 19G water-cooled monopolar RFA needle and a dedicated generator system.Results After a multidisciplinary discussion, the lesion was ablated in two different sessions, which resulted in destruction of about 70 % of neoplastic tissue. A second step surgery was required but initially refused by the patient.Conclusions EUS-RFA could be an effective way to treat left hepatic lesions not manageable with conventional percutaneous methods. This case report does not highlight concerns about safety of this approach and this observation needs to be validated in a larger cohort of patients with cirrhosis.